Application of rock physics parameters for lithology and fluid prediction of ‘TN’ field of Niger Delta basin, Nigeria - Chukwuemeka Patrick Abbey; Emele Uduma Okpogo; Ifeyinwa Obiageli Atueyi (Egyptian Journal of Petroleum)
Rock physics analysis was employed to predict the fluids and lithologic elements of ‘TN’ Field of Niger Delta. Sand and shale were delineated by the well log analysis and validated by the various crossplots. The Lamé parameters λ (incompressibility) and μ (rigidity) were employed to discriminate hydrocarbon filled sandstone from water filled sandstone. Gas sand, oil sand, brine and shale were all discriminated using the various rock physics cross plots. Sand is the predominant lithology in the near-surface while the percentage of shale increases with depth to a point where the percentage of shale exceeds that of sand. It was shown that shale has higher density value than sand across the field. Furthermore, the special arrangement of the reservoir fluids shows that brine has the highest density and gas has the lowest. The lowest density and lambda rho region represents the gas zone which is characterized by low compressibility. Velocity ratio log reveals some pitfalls in gamma ray lithology description when taken into consideration the corresponding resistivity log. However, although gamma ray is a better lithology indicator than velocity ratio, in a case of ambiguity, velocity ratio is necessary to validate the result obtained from gamma ray analysis. Both Mu-rho and density are lithology discriminators but density has advantage over mu-rho when it comes to fluid prediction in reservoir. The cross plotted Lambda rho and mu-rho is effective as lithology and fluid discriminator. Keywords: Lithology, P-impedance, Formation, Incompressibility, Nigeria